Pengembangan Pegawai Melalui Pendidikan dan Pelatihan di Kantor Badan Perencanaan Pembangunan Kota Bandung - Supardi Supardi (Fakultas Ekonomi Universitas Panca Marga, 2019)
The development of the quality of Human Resources has a much-needed position in bridging the increasingly transparent and global world development. For this reason, there needs to be a strategy to improve the quality of human resources, which leads to the development of complete human resources both in the physical and spiritual fields. This is done through the process of education, training and coaching as well as the development made by every manager in an organization, both business and public organizations, structured and professional. Anyone who can ask to be returned to employees who have just come from participating in education and training is obliged to share the knowledge gained for all Bappeda officials. Periodic discussions also need to be intensified, where Bappeda officials discuss presentation material, especially regarding actual development and planning issues. Efforts such as this, increasing collective capacity, building teamwork, improving the quality of officers, also have the potential to reduce competition tension in staff. Keywords: Development, Employees, Education, Training